Qualifying Work Experience in England and Wales: The Opportunities and Risks Presented to University Law Clinics. (January 2023) - Todd, Andrea; Blackburn, Lucy
This commentary details the sweeping changes to the route to qualification as a solicitor in England and Wales brought about in September 2021 and considers the opportunities and risks presented to university law school clinics by one aspect of this route: the new system of Qualifying Work Experience (QWE). The article reflects on the opportunities for law clinic development, innovation and recognition offered by QWE and weighs these up against the potential risks that will need to be managed carefully to avoid them becoming a threat to law clinic enhancement. The article considers the results of an early data gathering exercise to garner clinician and student volunteer perspectives on QWE within its first year of operation.